Meeting between the Prime Minister and members of the Trades Union Congress General Council Special Industrial Committee (9.55 pm) (verbatim report) : (1926/04/30) - Trades Union Congress. General Council. Special Industrial Committee ; Baldwin, Stanley Baldwin, Earl, 1867-1947 Date
30 April 1926